Innovacion and teaching performance in a profesional teacher training institute - Yparraguirre Villanueva, Américo Roberto (2023)
The role of the teacher is fundamental in the training of a professional, therefore the objective was to establish the relationship between innovation and teaching performance of a professional pedagogical training institute. The study followed a quantitative route since the problem arises from the observation of the study phenomenon and measurements of the variables were carried out. The research was basic with a descriptive and correlational level, non-experimental design with a transactional nature. The instruments have validity and reliability. The sample was made up of 218 students from the institute. The results indicated that teaching innovation reaches a medium level with 59.2% and teaching performance a high level with 89.4%. For the inferential test, an inferential analysis was applied after evaluating the normality test which determined a non-parametric analysis with Spearman's Rho test whose result was 0.456 indicating a moderate, positive and significant relationship with Sig. = 0.004 < 0.05